Existential of Imigrant Family as A Social Identity and Cultural Value in The 'Minari' Film - suwandono, Luthfi Suwandono; Nafsika, Salsa Solli (Universitas Pendidikan Indonesia, 2023)
The presence of foreign immigrants in the United States is a social phenomenon born of internal and external factors. The existence of immigrants is a concept that describes ethnicity, social structure, and political policies in a country. In the context of the mass media, there are several framings of immigrants who are grouped in superpower society, one of which is in the media film Minari. The existence of Korean immigrant families raises cultural values in neighboring life and forms social identity by maintaining Eastern culture in the West. This study uses a qualitative method with a literature study approach and data sources obtained from the Minari film and indexed journals that discuss similar themes. The result of this research is the process of describing social identity through the characterizations contained in certain scenes in the film and identifying the cultural values contained therein. The conclusion that can be drawn is that social identity is identified from the character's motivation in achieving the American Dream work ethic and maintaining household relationships with local residents while learning a new culture.